Cervical cancer screening among immigrant women in Norway- The healthcare providers' perspectives - Kathy Ainul Møen; Laura Terragni; Bernadette Kumar; Esperanza Diaz (Taylor & Francis Group, 2018)
Objective: To explore health care providers' (HCPs) experiences regarding cervical cancer screening (CCS) among immigrant women, their strategies to facilitate these consultations and their need for further information. Design: Exploratory qualitative design. Setting: HCPs who perform CCS: general practitioners, midwives and private gynaecologists, working in Oslo, Norway. Subjects: We interviewed 26 general practitioners, 3 midwives and 3 gynaecologists. Method: Both focus groups and personal in depth semi structured interviews. Interview transcripts were analysed using a thematic analysis approach. Results: Some of the HCPs' experiences related to CCS were common for all women regardless of their immigrant background, such as the understanding of routines and responsibilities for prevention. Aspects specific for immigrant women were mainly related to organization, language, health literacy levels, culture and gender. Several strategies targeting organizational (longer consultations), language (using interpreters), health literacy (using anatomy models to explain) and culture (dealing with the expression of pain) were reported. Most HCPs had not previously reflected upon specific challenges linked to CCS among immigrant women, thus the interviews were an eye-opener to some extent. HCPs acknowledged that they need more knowledge on immigrant women's' reproductive health. Conclusion: HCPs' biases, stereotypes and assumptions could be a key provider-level barrier to low uptake of CCS test among immigrants if they remained unexplored and unchallenged. HCPs need more information on reproductive health of immigrant women in addition to cultural awareness.Key Points The participation rate of immigrant women to cervical cancer screening in Norway is low, compared to non-immigrants. This might be partly attributed to health care system and provider, and not only due to the women's preferences. Our focus groups and interviews among health care providers show, that in addition to cultural competence and awareness, they need knowledge on reproductive health of immigrants. We recommend an intervention targeting health care providers to close the gap in cervical cancer screening.